The empirical analysis of production-based entrepreneurship training model, readiness and locus of control towards students entrepreneurship self efficacy - Ganefri, Ganefri; Hidayat, Hendra; Yulastri, Asmar; Yondri, Surfa (International Journal of Research in Counseling and Education, 2021)
This research was conducted because the students' self-efficacy in entrepreneurship is still low. Production-based entrepreneurship training model, learning readiness is assumed to be a factor that affects student entrepreneurship self-efficacy. The purpose of this study was to examine the contribution of the production-based entrepreneurship training model, learning readiness, and locus of control to student entrepreneurship self-efficacy. This study uses quantitative methods with multiple regression. The population is all students who take the general course of entrepreneurship in Higher Education as many as 500 people, and a sample of 200 students who are selected using proportional stratified random sampling. The questionnaire stands as an effective data collection method to examine the variables to be measured and the answers expected by the respondents. The questionnaire applied the Likert scale by providing opportunities to answer each item. Data were analyzed using multiple regression. The research findings show that there is a joint contribution of the production-based entrepreneurship training model, learning readiness, and locus of control to the entrepreneurial self-efficacy of students